Je vous salue Marie de Jean-Luc Godard : modalités et enjeux d’un retour du religieux au cinéma - Natalie Malabre (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Is it possible to film religious subject, a very sensitive one like the virginity of Mary, out of the references of religious stances? That was the challenge of Jean-Luc Godard in the middle of the 80’s when he promoted “Je vous salue Marie”. Without surprise, some Catholics demonstrated their opposition. But some of them tried to explain and support the untraditional way to approach the mystery of transcendence.